The influence of online celebrity live streaming e-commerce on consumers’ purchase intention - Ziru Hong (2022)
Live streaming e-commerce has exploded in China as a result of the videoization of social networks，becoming an increasingly important marketing tool, where the streamers are frequently Internet celebrities. Previous research has looked at the aspects that influence customers' purchase intentions in live streaming e-commerce. In this study, variables are summarized by combining live streaming features and the celebrity effect of Internet celebrities, and hypotheses are suggested using the SOR model. The goal is to investigate what factors influence consumers' purchase intentions when they watch Internet celebrities in live streaming e-commerce. This study distributed surveys, collected 305 valid questionnaires, and then utilized the tools SPSS.26 and SmartPLS 4.0 to estimate the model. The results demonstrate that the Internet celebrity's interactions, promotion discount, and attractiveness have a significant impact on customers’ purchase intention, with Social Presence and Emotions acting as mediator in the internet celebrity live streaming e-commerce. Finally, towards the end of the work, the theoretical contribution, practical implications, limitations, and future research suggestions are summarized. This study examines the influencing elements of live streaming e-commerce on customers' buy intentions from the standpoint of online celebrity mixed with live streaming, however it does not examine the moderating influence of different commodity categories.